Effects of climate change and adaptive options for maize–wheat rotations in the North China Plain: a model-based evaluation - Meng, Lingchao; Li, Zhicheng; Su, Lei; Ren, Haiwen; Han, Sheng; Zheng, Yunfei (Frontiers in Agronomy, 2026)
Climate change threatens the stability of crop production in the North China Plain (NCP), a major grain-producing region in China. Assessing crop responses to future climate change and the effectiveness of adaptive strategies is essential for sustaining regional food security. We used calibrated DSSAT–CERES models for maize and wheat to simulate phenological development and yield under future climate scenarios. Simulations were conducted for the 2050s and 2080s across multiple Shared Socioeconomic Pathway (SSP) scenarios, incorporating projected changes in temperature, solar radiation, and precipitation. Adaptive measures, including optimized sowing dates and alternative cropping systems, were evaluated. By the 2080s, the NCP is projected to experience pronounced warming, with maximum and minimum temperatures increasing by 2–6 °C and 0.4–3 °C, respectively, alongside increases of 0.3–0.8 MJ m⁻² in solar radiation and 280–430 mm in precipitation. Climate warming advanced anthesis and maturity by up to 12 and 21 days for summer maize and 28 and 14 days for winter wheat, leading to substantial yield reductions (17–82% for maize and 26–36% for wheat). Maize was more sensitive to warming than wheat. Optimized sowing dates increased maize yields by up to 90% and improved maize–wheat rotation yields by 20–35%, while single cropping further increased maize yields by 43–113% and wheat yields by 5–40%. Although climate change is projected to substantially reduce crop yields in the NCP, targeted management and cropping system adjustments can effectively mitigate yield losses and enhance agricultural resilience.